A world of opportunity: A top-down influence of emotional intelligence-related contextual factors on employee engagement and exhaustion - Levitats, Zehavit; Ivcevic, Zorana; Brackett, Marc (Frontiers in Psychology, 2022)
Despite continuing interest in the impact of employees’ emotional intelligence (EI) in explaining for their engagement and emotional exhaustion, there are still large gaps in our understanding of the role played by contextual EI-related factors, such as an EI-related organizational culture and supervisors’ emotionally intelligent behavior (EIB). This two-study research approaches EI from a macro-level perspective, attempting to address three objectives: (1) to develop and define a theoretical concept of EI-supportive organizational culture, (2) to develop and validate measures of organizations’ EI-related values and practices, and (3) to investigate their top-down effect on employee engagement and exhaustion, via supervisor EI-related behavior. In the first study, we conceptualize and develop measures of perceived EI-related organizational values and human resource management (HRM) practices, as separate yet related dimensions of organizations’ EI-related culture, and test their validity. In the second study, we build on the job demands-resources (JD-R) theory and Ability-Motivation-Opportunity (AMO) framework to develop and test a model of the process links between perceived EI-related values and HRM practices and employee engagement and exhaustion, using a large sample of employees across industries in the USA workforce (N = 12,375). In line with our hypotheses, the findings suggest that EI-supportive HRM practices have a top-down effect on employee engagement and exhaustion via supervisor EIB, whereas low regard for emotions values has a top-down effect on employee exhaustion via supervisor emotional misbehavior. Results are discussed in the context of the JD-R theory, AMO framework, and the EI literature.